The ‘surprise’ question in haemato-oncology: the estimating physician and time to death reduce the prognostic uncertainty - an observational study - Gerlach, Christina; Weber, Martin; Schmidtmann, Irene (Cancers, 2025)
Background/Objectives: Patients with haematological malignancies less frequently receive specialist palliative care, although they may have unmet needs for symptom control and alleviating psychosocial and existential burdens. The ‘Surprise’ Question, ‘Would you be surprised if this patient died in the next 12 months?’, helps physicians to identify patients who may benefit from palliative care. We tested the influencing factors of the feasibility of the ‘Surprise’ Question in haemato-oncology outpatients. Methods: We performed a prospective cohort study comparing patients with solid tumours and haematological malignancies. All the patients in the haemato-oncology outpatient clinics of a German university hospital were screened by haemato-oncologists using the ‘Surprise’ Question. Results: A survival analysis was performed on 672 patients (76% with haematological malignancies) at 3 and 12 months. Within one year, 110 patients (16%) died. Of these, 30/52 (58%) were patients with solid tumours, but only 12/53 (23%) patients with haematological malignancies were identified in advance by the ‘Surprise’ Question, which reflects ambiguous test sensitivity. A substantial part of the haematology patients in their last year of life were not identified (77%). The match between the survival estimates and actual outcomes was fair (Cohen’s kappa 0.37). The proximity from prediction to event and the estimating physician rather than patient characteristics influenced the accuracy of the instrument. Conclusions: For the first time, the feasibility of the ‘Surprise’ Question in haematology outpatients was proven. Factors that would improve haemato-oncologists’ clinical intuition should be further explored to facilitate timely conversations about issues important to patients nearing the end of life.
Gesehen am 25.09.2025